Anticarcinogenic effects of halofuginone on lung-derived cancer cells - KARADENİZ CERİT, KIVILCIM (WILEY, 2020)
Malignant mesothelioma is a rare but aggressive form of malignancy, which is difficult to diagnose and is resistant to current chemotherapeutic treatment options. Molecular techniques have been used to investigate the mechanisms of action and the beneficial therapeutic effects of halofuginone (HF) in several cancers but not malignant mesotheliomas. In this study, the antiproliferative and apoptotic effects of HF were investigated through its ability to deregulate EGFR downstream signalling cascade proteins in the pathologically aggressive malignant mesothelioma and non-small-cell lung cancer cells. We showed that administration of HF at nanomolar concentrations induced a dose-dependent reduction in the viability of cancer cells, made cell cycle arrest, inhibited proliferation of cancer cells via STAT3 and ERK1/2 pathways and triggered the apoptotic cascade via p38MAPK. We demonstrated that the apoptotic cell death mechanism was mediated by enhanced activation of caspase-3 and concomitant PARP cleavage, downregulation of Bcl-2 and upregulation of Bax in both malignant mesothelioma and lung cancer cells. In particular, we demonstrated that cancer cells were more sensitive to HF treatment than normal mesothelial cells. Taken together, this study suggests that HF exerts its anticancer effects in lung-derived cancers by targeting signal transduction pathways mainly through deregulation of ERK1/2, STAT3 and p38MAPK to reduce cancer cell viability, induce cell cycle arrest and apoptotic cell death. Thus, HF might be considered as a potential agent against malignant mesothelioma and/or lung cancer cells.
Keywords: AKT; apoptosis; halofuginone; malignant mesothelioma; MAPK; STAT3; PHASE-II; MALIGNANT MESOTHELIOMA; GROWTH-INHIBITION; TUMOR-GROWTH; ANGIOGENESIS; SUPPRESSION; ACTIVATION; EXPRESSION; APOPTOSIS; FIBROSIS